BENEFICAL THERAPEUTIC EFFECT OF CHINESE HERBAL XINJI′ERKANG FORMULA ON HYPERTENSION-INDUCED RENAL INJURY IN THE 2-KIDNEY-1-CLIP HYPERTENSIVE RATS - Ling-ling, Huang; Chen, Pan; Tingting, Yu; Kun, Guo; Chaozong, Lan; Xinghui, Wang; Shan, Gao (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Increase in evidence shows that the role of kidney injury in hypertension is important. Xinji′erkang (XJEK), a Chinese herbal formula, has been identified as an effective preparation in the treatment of coronary heart disease and myocarditis. We have previously demonstrated that XJEK attenuate oxidative stress and hypertension target organ damage. The aim of this study was to assess the renal protective function of XJEK.Materials and Methods: Two Kidney One Clip (2K1C) model was adopted to induce hypertension in rats. We submitted male Sprague Dawley (150-180) g rats to either renal artery clipping or sham operation. Renal hypertension was established after four weeks of surgery. Rats were randomized divided into the four groups: sham-operated group (Sh-Op) (n=10), two-kidney, one-clip hypertension group (2K1C) (n=10), Xinji′erkang treatment group (XJEK) (n=10) and Fosinopril (n=10) treatment group. Drugs were administered orally daily for four weeks. Systolic pressures were measured every week using the tail-cuff apparatus. 24h before death, urine samples were collected for detect of urinary proteins. The kidney weight (KW) index was expressed as kidney weight/body weight (KW/BW). The histological changes were investigated by hematoxylin and eosin and Van Gieson staining. Immunohistochemical assay was employed to observe the intra-renal transforming growth factor-β1 (TGF-β1) protein expression. Serum creatinine (SCR) and blood urea nitrogen (BUN) were assayed by automatic biochemical analyzer. ELISA kit was used to assay Angiotensin II (Ang II) and TGF-β1 content in serum. Results: Administration of XJEK markedly alleviated the rise in blood pressure and declined LKW/BW ratio. Histo-pathological injuries including hypertrophic glomerular, glomerular sclerosis, glomerular and interstitial fibrosis were attenuated. XJEK also decreased SCR, BUN, urinary proteins in 24h urine, serum Ang II and TGF-β1 concentrations and the intra-renal TGF-β1 protein expression. Conclusion: XJEK therapy in the 2K1C hypertensive rats affects the rise in blood pressure and ameliorates the severity of kidney injury. The protective effect is most likely due to the ability of XJEK to affect the Renin-Angiotensin-Aldosterone System (RAAS) and the TGF-β systems.